1997
DOI: 10.1093/nar/25.9.1825
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerization catalysed by a group II intron RNA in vitro

Abstract: The excised group II intron bI1 from Saccharomyces cerevisiae can act as a ribozyme catalysing various chemical reactions with different substrate RNAs in vitro . Recently, we have described an editing-like RNA polymerization reaction catalysed by the bI1 intron lariat that proceeds in the 3'-->5'direction. Here we show that the bI1 lariat RNA can also catalyse successive deoxyribonucleotide polymerization reactions on exogenous substrate molecules. The basic mechanism of the reaction involved interacting cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It has already been demonstrated that ribozymes are capable of acting on DNA. Group II introns have been demonstrated to be capable of DNA -polymerization,‖ generating longer DNA oligos via successive transesterification reactions, as well as DNA ligation (Hetzer et al 1997). In addition, a minimal number of mutations allow RNA enzymes to perform catalysis on either RNA or DNA (Beaudry & Joyce 1992).…”
Section: List Of Tablesmentioning
confidence: 99%
“…It has already been demonstrated that ribozymes are capable of acting on DNA. Group II introns have been demonstrated to be capable of DNA -polymerization,‖ generating longer DNA oligos via successive transesterification reactions, as well as DNA ligation (Hetzer et al 1997). In addition, a minimal number of mutations allow RNA enzymes to perform catalysis on either RNA or DNA (Beaudry & Joyce 1992).…”
Section: List Of Tablesmentioning
confidence: 99%